Effects of different fruit freeze-dried powders on the 3D printing properties of peach gum-based gummy candy gels - Ye-Xing Liang; Jing-Bing Xu; Li Zhou; Xue Li; Ling Zhang; Fan-Bing Meng (Food Chemistry: X)
The rheological properties and 3D printing effects of different composite gels were explored, and the results revealed that the viscosity of the peach gum polysaccharide and gelatin composite gel (PGP/GE)was moderate, and had the best 3D printing quality and stability. Using PGP/GE as the 3D printing substrate and adding five types of freeze-dried fruit powders. Strawberries, mangoes, and yellow peaches had better water binding abilities than sea buckthorn and mulberries did; as the amount of fruit powder added increased, its ability to bind water increased. The 3D printing quality of mulberries and sea buckthorn was inferior to that of yellow peaches, strawberries, and mangoes. The printing effect of the low-dose fruit powder groups (5 g, 16.67 % w/v) were better than those of the high-dose groups (10 g, 33.33 % w/v). Through texture and sensory analysis, the low-dose fruit powder groups had better taste, especially the low-dose strawberry compound gel group.